One-stop endovenous laser ablation leads to superior outcomes for varicose veins and iliac vein compression - Hong Chen; Chuang Wang; Shenglin Ye; Lulu Wang; Xiaoqiang Li; Lingshang Kong; Xian Zhu; Xiaolong Du; Nan Hu (Scientific Reports)
Abstract To retrospectivly investigate the short-term clinical outcomes of one-stop and two-staged endovenous laser ablation (EVLA) procedures for treatment of varicose veins (VVs) and iliac vein compression syndrome (IVCS). In this study, 424 patients were treated for VVs and IVCS from June 2017 to June 2020, 91 underwent one-stop stent angioplasty (SA) and EVLA, 132 underwent two-staged SA and EVLA, 104 underwent one-stop balloon angioplasty (BA) and EVLA, and 97 underwent two-staged BA and EVLA. Clinical outcomes and complications were recorded at 3 and 12 months post-intervention. Quality of life (QoL) was assessed with the venous clinical severity score (VCSS) and Villalta scale. Patients in the SA groups were older (p < 0.05) with higher BMI values (p < 0.05). The incidences of iliac vein stenosis (p < 0.001) and recurrent VVs (p < 0.01) were lower in the one-stop SA group. The VCSS was significantly improved (p < 0.05) at 12 months after the one-stop SA procedure. The one-stop SA procedure effectively relieved symptoms, decreased symptom recurrence, and improved the QoL of patients with VVs and severe IVCS. The two-staged BA procedure is recommended for patients with longer life expectancy.